DIFFERENCES IN SITUATIONAL EFFICIENCY PARAMETERS BETWEEN WINNING AND LOSING TENNIS PLAYERS AT THE AUSTRALIAN OPEN - Vladimir Ivanek; Branimir Mikić; Stanislav Dragutinović (Sport Scientific And Practical Aspects, 2026)
The Australian Open, together with Wimbledon, Roland Garros and the US Open, is one of the four biggest tournaments known as Grand Slams. As the first major tournament of the year, it is a very important and prestigious event. Since it is held immediately after the preparation period, players are expected to show a high level of physical, technical-tactical and psychological preparedness. It is played on a hard surface, which additionally increases the physical demands placed on tennis players. The aim of this research is to determine whether there is a statistically significant difference in the “winner” points achieved between winning and losing tennis players at the 2024 Australian Open. The study analyzed situational efficiency parameters between winners and losers. The sample of variables consisted of 246 players in 123 matches played at the 2024 Australian Open. All matches that were completed were included in the research; four matches ended with the retirement of one of the players and were therefore not included in order to obtain valid data in the final statistical analysis. The results were obtained based on the analysis of points won during the match, using seven (7) different tennis strokes. Discriminant analysis of the obtained data showed that there are statistically significant differences between winning and losing tennis players in certain tennis strokes. The results showed that the greatest difference was in the “overhead” stroke, in favor of the winners.